Reparación de daños por violación de la confianza y esperanzas legítimas: un análisis de los sistemas jurídicos Francés y Colombiano (2021)
Legitimate expectation implies the belief or intimate conviction that an administrative procedure can be maintained without any changes or surprises in order to achieve its objectives. This circumstance generates legitimate expectations regarding the likelihood of obtaining a right, that is, a future right or a right in the process of consolidation. To this extent, trust and legitimate expectations are sometimes frustrated, causing pecuniary damage to those involved in the administrative procedure and generating what the Colombian legal system has called unlawful damage, that is, that can be compensated. This circumstance makes it possible to analyze the functioning of the State’s liability in France and Colombia, when damages that can be compensated occur. This is reflected in the recognition of future rights or in the process of consolidation or in the corresponding economic compensations.